Analyzation of Digital Marketing on Hotel Performance in Malaysia - Iskandar Zulkarnain, Adam; Ridzuan, Abdul Rauf; Hafifi Jamri, Mohamad; Djuyandi, Yusa; Zul Chairiyah, Sri (Public Knowledge, 2025)
Technology and innovation are pivotal in advancing the tourism sector and shaping tourist activities in Malaysia. In response to challenges such as social distancing and safety regulations following the COVID-19 pandemic, chain hotels are forced to find new ways to attract customers. Since digital tools greatly impact tourists' accommodation decisions, it's crucial for hotels to be adaptable in their digital marketing efforts. Hotels that do not leverage digital marketing are missing out on significant opportunities to grow their business and enhance their market presence. Tower Regency Hotel in Ipoh, Seri Malaysia and Syeun Hotel have seen a decrease in the number of guests checking in, which directly affects their business because they do not use digital marketing as much as other hotels that can survive over the long term, like Impiana Hotel Ipoh, MRoof Hotel, Weil Hotel and MH Hotel. Therefore, this study aims to identify the most effective digital marketing strategy to enhance hotel performance in Malaysia. Researcher use a systematic review method, taking into account potential articles published from January 2021 to May 2024 on encompassed renowned open-access journals and platforms, such as Wiley Online, Emerald, Google Scholar, Taylors and Francis Online, Elsevier and Springer Link, along with other relevant online articles retrieved via Google search. Variations in the terms used in this research include digital marketing strategies, service quality and hotel performance. Results indicate that the most impacted digital marketing strategies and services on hotel performance are user-friendly websites and apps, mobile check-in/check-out, digital keys and 24/7 customer service. Future research should improve studies on the benefits of digital marketing strategies on customer satisfaction and service quality